Pelatihan Dasar Programming Pembuatan Game Menggunakan Scratch Sebagai Upaya Kesiapan Menghadapi Industri Kreatif - Natsir, Fauzan; Sihombing, Redo Abeputra; Triyadi, Triyadi (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
Human Resources needed in the Industrial Age 4.0 must have at least 5 main competencies including critical thinking and problem-solving. The Indonesian government through the Ministry of Education and Culture plans to include two additional competencies in the education curriculum in Indonesia, namely Computational Thinking (CT) and Compassion. Computational thinking is considered one of the basic competencies to complete these skills. Computational Thinking and Compassion additional competencies are needed to face the digital technology era. But on the other hand, teacher and student knowledge about computational thinking is still very minimal. Some elementary schools still do not utilize technology to encourage students' thinking skills. One way to practice these skills is to teach programming to early childhood. Among the methods that can be used to introduce computational thinking to elementary school, students are workshops and training activities. Therefore, the objectives of this activity are to educate students on how to use the Scratch application to introduce mathematical and computational thinking in elementary schools and to provide hands-on experience for students in introducing simple programming concepts by creating animation projects and games. The results that students get after attending this training are an increased understanding and experience of how to use computers and students can make simple animations and games with the Scratch application.